Diagnosing dementia in the Arctic: translating tools and developing and validating an algorithm for assessment of impaired cognitive function in Greenland Inuit. (1st June 2022) - Kleist, I.; Noahsen, P.; Gredal, O.; Riis, J.; Andersen, S.
Abstract : Introduction: The ageing Arctic populations raise the need for work-up of cognitive function that reflects language and cultural understandings. Objectives: To translate and evaluate tools for work-up of cognitive impairment in Greenland. Methods: Step A: An expert panel was established to select tools suitable for the work-up of cognitive impairment at three different settings in Greenland. Step B: Tools were translated in a multiple-step process of independent translations with back-translation and adaptations by two independent translators and two Greenlandic physicians. Step C: a testing and validation process of the tools at three locations: the national hospital in the capital city; regional hospital in a town; health care centre in a small town. Results: Tools selected were Mini-Cog and RUDAS. Participants for testing of tools were 43 of 61 invited, of which six had dementia. RUDAS and Mini-Cog scores were associated (p < 0.001). The smoothed AUC was 0.87 (95%-CI, 0.65–0.95) for Mini-Cog and 0.90 (95%-CI, 0.76–0.97) for RUDAS. The sensitivity of Mini-Cog with a cut-off at ≤3 was 83.3%, and specificity was 62.2%. For RUDAS with a cut-off at ≤23, these were 100% and 75.7%, respectively. Conclusions: Requested tools have been translated for assessing cognitive function in the native Arctic setting. Small town residents with a Mini-Cog score of 3 or lower should be referred to a regional hospital for RUDAS, and a score of 23 or less should cause referral to the national hospital for a full work-up of cognitive function. Disclosure: No significant relationships.